DINAMIKA HUKUM INTERNATIONAL SEBAGAI SUBSTANSI ETIKA ANTAR NEGARA DI DUNIA - Sang Made Merta Widnyana; Komang Febrinayanti Dantes; Si Ngurah Ardhya; Muhamad Jodi Setianto (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2022)
The purpose of this paper is to provide an understanding of International Law that is reviewed in general through research and study by experts and characteristics related to International Law with a view on the behavior and relations between countries regarding the application of International Law In the past and in times like the present that have undergone several processes of globalization that cause changes in the times and changes in the behavior of every society in the country related to aspects of International Law.Based on the results of the discussion that can be concluded that all kinds of actions and behaviors of objects and subjects in International Law is a discussion that becomes a real point in International Law ranging from Relations between States, International Organizations, Individuals, or even Companies struggling in the multinational field are things discussed and reviewed in International Law.